Analytic Hierarchy Process (AHP) for car purchasing selection among UiTM’S students / Siti Amirah Che Abd Halim, Wanifildatul Athirah Zulkiplee and Zurul Nurain Esa - Che Abd Halim, Siti Amirah; Zulkiplee, Wanifildatul Athirah; Esa, Zurul Nurain (2023)
Analytic hierarchy process (AHP) is used when making decisions with many criteria. AHP provides a structure for decision-making procedures where there are a limited number of options, but each has several attributes. This paper explores the use of AHP for deciding on car purchase among UiTM's students. Buying a car can appear to be a difficult task because it is influenced by a lot of factors such as family income, safety concerns, the number of automobiles in the family, additional financial commitments, and so on. Hence, the objective is to determine the important criteria for car purchasing selection using the Analytic Hierarchy Process (AHP) method and to identify the preferred models of cars among students of Universiti Teknologi MARA (UiTM) using the Analytic Hierarchy Process (AHP) method. To achieve the study's goal of finding the important aspect in choosing a vehicle and the preferred car types by applying the AHP approach, a survey was conducted. These were carried out by questioning UiTM Seremban, Negeri Sembilan students. This survey was carried out in a series of steps, From the research finding of Analytic Hierarchy Process (AHP) method we can conclude the important criteria for car purchasing selection is Criteria 5, price. the preferred models of cars among students of Universiti Teknologi MARA (UiTM) is Alternative 3, Perodua. The Analytic Hierarchy Process (AHP) might be recommended as one of the solutions in future studies to address the issue with AHP methods. Any business or organization may benefit from using AHP since it provides a method for decision making when there are limited choices, but each has a variety of attributes.